Intrachoroidal Neovascularization in Transgenic Mice Overexpressing Vascular Endothelial Growth Factor in the Retinal Pigment Epithelium - Schwesinger, Catherine (American Society for Investigative Pathology, 2001)
Choroidal neovascularization in age-related macular degeneration is a frequent and poorly treatable cause of vision loss in elderly Caucasians. This choroidal neovascularization has been associated with the expression of vascular endothelial growth factor (VEGF). In current animal models choroidal neovascularization is induced by subretinal injection of growth factors or vectors encoding growth factors such as VEGF, or by disruption of the Bruch’s membrane/retinal pigment epithelium complex with laser treatment. We wished to establish a transgenic murine model of age-related macular degeneration, in which the overexpression of VEGF by the retinal pigment epithelium induces choroidal neovascularization. A construct consisting of a tissue-specific murine retinal pigment epithelium promoter (RPE(65) promoter) coupled to murine VEGF(164) cDNA with a rabbit β-globin-3′ UTR was introduced into the genome of albino mice. Transgene mRNA was expressed in the retinal pigment epithelium at all ages peaking at 4 months. The expression of VEGF protein was increased in both the retinal pigment epithelium and choroid. An increase of intravascular adherent leukocytes and vessel leakage was observed. Histopathology revealed intrachoroidal neovascularization that did not penetrate through an intact Bruch’s membrane. These results support the hypothesis that additional insults to the integrity of Bruch’s membrane are required to induce growth of choroidal vessels into the subretinal space as seen in age-related macular degeneration. This model may be useful to screen for inhibitors of choroidal vessel growth.